One-pot oxidative cleavage of cyclic olefins for the green synthesis of dicarboxylic acids in Pickering emulsions in the presence of acid phosphate additives. Issue 19 (1st September 2020) - Yang, Bingyu; Douyère, Grégory; Leclercq, Loïc; Nardello-Rataj, Véronique; Pera-Titus, Marc
Abstract : Dicarboxylic acids were prepared by the oxidative cleavage of cyclic alkenes by adsorbing dodecyltrimethylammonium phosphotungstate particles and silica particles functionalized with octadecyl chains and sulfonic acid groups at the W/O interface. Abstract : Dicarboxylic acids were prepared by the one-pot oxidative cleavage of cyclic alkenes with aqueous H2 O2 by adsorbing dodecyltrimethylammonium phosphotungstate nanoparticles, and silica particles functionalized with octadecyl chains and sulfonic acid groups, C18 /C3 SO3 H, at the W/O interface. Na2 HPO4 and [C12 ]H2 PO4 conditioned the interlocking and self-assembly of the particles, enhancing the catalytic selectivity, especially for cyclooctene.